Istikhdām Ṭarīqah Drill Bi aṣ-Ṣuwar aṡ-Ṡābitah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Saiṭarah al-Mufradāt al-`Arabiyyah (Baḥṡ Tajrībī Fī al-Madrasah aṡ-Ṡānawiyyah Fajar Hidāyah Bi Aceh Besar) - Muhammad Muhammad; Zulhelmi Zulhelmi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
Vocabulary is the most important element in learning Arabic. In teaching this lesson, the teacher must use suitable teaching methods and image media to achieve the goals of the study, unless it fails. For instance, some second-grade students of junior high school in Fajar Hidayah Islamic boarding school studied vocabulary but some of them could not apply it in oral or written Ta'bir. The main problem is due to the teacher has not practiced suitable methods yet in teaching vocabulary. In order to solve the problem, the researcher applied the method of drill and image media in teaching vocabulary to the students of junior high school in Fajar Hidayah Islamic boarding school. The purpose of this research is to know the students' response to vocabulary learning by applying drill methods and image media and the effectiveness of its application to improve the ability of students in the study of vocabulary. The used method was quasi-experimental designs. The study population is all students of the junior high school Fajar Hidayah and samples are second graders amounting to 22 students. The results showed that students ' responses to vocabulary learning by applying drill methods and image media were very good and the implementation was effective in improving the students ' ability to control the Mufradat in the integrated Islamic School of Dawn Hidayah, evidenced by the T-count value greater than T-table.